Pengaruh Governance terhadap Firm Value dengan Institutional Ownership sebagai Variabel Moderasi pada Perusahaan Cyclicals dan Non-Cyclicals di BEI 2021-2023 - Elda Furi Lestari; Ambar Kusumaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The study investigates the impact of governance on firm value, along with the moderating role of institutional ownership, among companies operating in the consumer cyclicals and consumer non-cyclicals sectors listed on the Indonesia Stock Exchange (IDX) over the 2021-2023 period. Drawing on a sample of 42 companies and 126 observations, a quantitative panel data approach was adopted, with data gathered through purposive sampling. The Bloomberg Governance Score was used to measure governance, Tobin's Q served as a proxy for firm value, institutional ownership was the moderating variable, and firm size, leverage, and profitability were included as control variables. Model selection was conducted using the Chow and Hausman Tests in EViews 14, which indicated that the Random Effects Model (REM) was the most suitable estimation approach. The findings reveal that governance does not exert a significant influence on firm value. Furthermore, institutional ownership is unable to strengthen the relationship between governance and firm value. These results suggest that ESG-based governance signals have not yet been optimally absorbed by investors in the Indonesian capital market; hence, reinforcing governance reporting standards and enhancing investor ESG literacy are considered essential steps toward integrating non-financial information into investment decision-making.